Formulation of Liquid Biofertilizer for Enhance of Soil Nutrients in Peatland - Liswara Neneng (Budapest International Research and Critics University, 2020)
The main problem of peatland utilization was low fertility of land. The plant growth promoting microorganisms thrive in soils naturally, but their populations are scarce. Optimation and implementation of fertilizer based on beneficial microbes having potential to enhance the solubility of soil nutrients and to increase of yield crop. This study aims were to examine: 1) the effectiveness of liquid media for enchance of biofertilizer potency; 2) composition of liquid biofertilizer which potential for enchance of soil nutrients in peatland. This research was an experimental research in a field. Independent variables consist of: 8 compositions of liquid biofertilizer, included positive control (EM4), and negative control (aquadest), with 3 replication of each. Dependent variables were soil nutriens, namely: N, P, K,C. Soil nutriens measured following method of Soil Analysis procedure, using AAS. All data were analysed using ANOVA statistical method. The results showed: liquid media composed by 15% of sugar and 85% of coconut water, better more to support of biofertilizer potency for enhanced of soybean growth in peatland. Composition microbes KHY +IBT better more for increase of pottasium (K-dd) content and N-Total in peatland, compared than another compositions. Treatment with liquid biofertilizer from local microorganisms, had increased of soil nutrients N-total 69,7%, phosphate 4,7%, and potassium 28%, compared with negative control. Composition of potential microorganisms in liquid biofertilizer were Pseudomonas sp., Bacillus sp., Kebsiella sp., Aspergillus sp., Azotobacter sp.